Endogenous insulin signaling in the RPE contributes to the maintenance of rod photoreceptor function in diabetes. (March 2019) - Tarchick, Matthew J.; Cutler, Alecia H.; Trobenter, Timothy D.; Kozlowski, Michael R.; Makowski, Emily R.; Holoman, Nicholas; Shao, Jianning; Shen, Bailey; Anand-Apte, Bela; Samuels, Ivy S.
Abstract: In diabetes, there are two major physiological aberrations: (i) Loss of insulin signaling due to absence of insulin (type 1 diabetes) or insulin resistance (type 2 diabetes) and (ii) increased blood glucose levels. The retina has a high proclivity to damage following diabetes, and much of the pathology seen in diabetic retinopathy has been ascribed to hyperglycemia and downstream cascades activated by increased blood glucose. However, less attention has been focused on the direct role of insulin on retinal physiology, likely due to the fact that uptake of glucose in retinal cells is not insulin-dependent. The retinal pigment epithelium (RPE) is instrumental in maintaining the structural and functional integrity of the retina. Recent studies have suggested that RPE dysfunction is a precursor of, and contributes to, the development of diabetic retinopathy. To evaluate the role of insulin on RPE cell function directly, we generated a RPE specific insulin receptor (IR) knockout (RPEIRKO) mouse using the Cre-loxP system. Using this mouse, we sought to determine the impact of insulin-mediated signaling in the RPE on retinal function under physiological control conditions as well as in streptozotocin (STZ)-induced diabetes. We demonstrate that loss of RPE-specific IR expression resulted in lower a- and b-wave electroretinogram amplitudes in diabetic mice as compared to diabetic mice that expressed IR on the RPE. Interestingly, RPEIRKO mice did not exhibit significant differences in the amplitude of the RPE-dependent electroretinogram c-wave as compared to diabetic controls. However, loss of IR-mediated signaling in the RPE reduced levels of reactive oxygen species and the expression of pro-inflammatory cytokines in the retina of diabetic mice. These results imply that IR-mediated signaling in the RPE regulates photoreceptor function and may play a role in the generation of oxidative stress and inflammation in the retina in diabetes. Highlights: Insulin signaling in the RPE is required for maintenance of the light-evoked responses of photoreceptors during diabetes. Diabetes-induced defects in the RPE-dependent c-wave of the ERG, occur with or without IR-mediated signaling in the RPE. Loss of insulin signaling in the RPE protects the diabetic retina against oxidative stress and inflammation.